STRUKTUR DAN DOMINANSI TEGAKAN DI ARBORETUM FAKULTAS KEHUTANAN UNIVERSITAS LAMBUNG MANGKURAT - Melitania Puspitasari; Udiansyah Udiansyah; Suyanto Suyanto (Universitas Lambung Mangkurat, 2023)
Research on Structure and Dominance of Forest in Arboretum Faculty of Forestry aims to analyze the forest structure and dominance in arboretum area Faculty of Forestry, University of Lambung Mangkurat. The method used in this study is sampling method with a model of continuous line plots. Forest structure analysis is tabulation method and dominance analysis using significant value index. Based on the results of the analysis at the arboretum Faculty of Forestry, University of Lambung Mangkurat it was found that 32 species were found, 17 species at seedling level, 15 species at sapling level, 18 species at pole level and 5 species at tree level. The seedling rate was dominated by Bridelia tomentosa 32,31%, the sapling level was dominated by Aporasa spp. 69,19%, the pole level was dominated by Aquilaria malaccensis 66,62% and the tree level was dominated by Acacia mangium 208,15%. Analysis of the stand structure in the arboretum area Faculty of Forestry both inside and outside the sampling found 46 species with a total of 92 individuals, the pole level of 70 individuals and the tree level of 84 individuals. Stand structure according to growth rate shows that the arboretum of the Faculty of Forestry is a type of secondary natural forest with a distribution like the concept of an inverted “J”. It is suggested that in arboretum area Faculty of Forestry it is necessary to regulate the species composition, spacing and number of each species to maximize the function of the arboretum as a collection of treesPenelitian tentang Struktur Dan Dominansi Tegakan di Arboretum Fakultas Kehutanan bertujuan untuk menganalisis struktur tegakan dan dominansi yang berada di area arboretum Fakultas Kehutanan Universitas Lambung Mangkurat. Metode yang digunakan dalam penelitian ini adalah metode sampling dengan model plot berbentuk jalur berpetak. Analisis struktur tegakan adalah metode tabulasi dan analisis dominansi menggunakan indeks nilai penting. Berdasarkan hasil analisis di arboretum Fakultas Kehutanan Universitas Lambung Mangkurat yaitu ditemukan secara samping ditemukan 32 jenis, 17 jenis tingkat semai, 15 jenis tingkat pancang, 18 jenis tingkat tiang dan 5 jenis tingkat pohon. Tingkat semai didominansi oleh jenis Bridelia tomentosa 32,31%, tingkat pancang didominansi oleh Aporasa spp. 69,19%, tingkat tiang didominansi oleh Aquilaria malaccensis 66,62% dan tingkat pohon didominansi oleh pohon Acacia mangium 208,15%. Analisis struktur tegakan di area arboretum Fakultas Kehutanan baik yang di dalam dan di luar sampling ditemukan 46 jenis dengan jumlah 460 individu dari tingkat semai 214 individu, tingkat pancang 92 individu, tingkat tiang 70 individu dan tingkat pohon 84 individ. Struktur tegakan menurut tingkat pertumbuhan menunukkan arboretum Fakultas Kehutanan merupakan tipe hutan alam sekunder dengan sebaran seperti konsep “J” terbalik. Disarankan bahwa di area arboretum Fakultas Kehutanan perlu dilakukan pengaturan komposisi jenis, jarak tanam dan jumlahnya masing-masing jenis untuk memaksimalkan fungsi arboretum sebagai koleksi pohon-pohon